ACCURATE DETERMINATION OF PERIARTICULAR BONE COMPOSITION IN HEALTHY INDIVIDUALS AND COMPARISON TO ACPA-POSITIVE RHEUMATOID ARTHRITIS PATIENTS - Simon, David; Kleyer, Arnd; Stemmler, F.; Simon, C.; Hueber, Axel; Kampylafka, E.; Englbrecht, Matthias; Figueiredo, C.; Engelke, Klaus; Berlin, Andreas; Haschka, J.; Rech, Jürgen; et al. (2016)
EVALuna2:13492

A comparative analysis of articular bone in large cohort of patients with chronic inflammatory diseases of the joints, the gut and the skin - Simon, David; Kleyer, Arnd; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Kocijan, Roland; Haschka, Judith; Hirschmann, Simon; Atreya, Raja; Neurath, Markus; Sticherling, Michael; et al. (Bone, 2018)
Chronic inflammatory diseases are associated with bone loss. While the occurrence of systemic bone loss is well described in chronic inflammatory diseases, the impact of these conditions on articular bone has not been systematically investigated. Recent refinements in high-resolution CT assessment of the joints now allow the accurate measure of articular bone composition. In this study 476 subjects comprising healthy individuals and patients with anticitrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA), ACPA-negative RA, Crohn's disease (CD), ulcerative colitis (UC), psoriasis (PsO) and psoriatic arthritis (PsA) were subjected to high-resolution quantitative computed tomography (HR-pQCT) of the hand. Metacarpal heads were assessed for total, trabecular and cortical volumetric bone mineral density (vBMD). Only ACPA+RA, but not the remaining inflammatory diseases (ACPA-RA, CD, UC, PsO, PsA) showed significant (p < 0.001) loss of articular bone affecting both the trabecular and the cortical compartments. Age and body mass index were also associated with articular bone changes, the former with lower, the latter with higher articular bone mass. In multivariate models, presence of ACPA+RA was an independent factor for articular bone loss. Among chronic inflammatory diseases ACPA+RA is the most potent precipitator for articular bone loss pointing out the role of autoimmunity in the development of articular bone disease in the context of chronic inflammatory disease.
EVALuna2:34480

Age- and Sex-Dependent Changes of Intra-articular Cortical and Trabecular Bone Structure and the Effects of Rheumatoid Arthritis - Simon, David; Kleyer, Arnd; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Hueber, Axel; Haschka, Judith; Renner, Nina; Figueiredo, Camille; Neuhuber, Winfried; Buder, Thomas; Englbrecht, Matthias; et al. (Journal of Bone and Mineral Research, 2016)
The objective of this cross-sectional study was to define normal sex- and age-dependent values of intra-articular bone mass and microstructures in the metacarpal heads of healthy individuals by high-resolution peripheral quantitative computed tomography (HR-pQCT) and test the effect of rheumatoid arthritis (RA) on these parameters. Human cadaveric metacarpal heads were used to exactly define intra-articular bone. Healthy individuals of different sex and age categories and RA patients with similar age and sex distribution received HR-pQCT scans of the second metacarpal head and the radius. Total, cortical, and trabecular bone densities as well as microstructural parameters were compared between 1) the different ages and sexes in healthy individuals; 2) between metacarpal heads and the radius; and 3) between healthy individuals and RA patients. The cadaveric study allowed exact definition of the intra-articular (intracapsular) bone margins. These data were applied in measuring intra-articular and radial bone parameters in 214 women and men (108 healthy individuals, 106 RA patients). Correlations between intra-articular and radial bone parameters were good (r = 0.51 to 0.62, p < 0.001). In contrast to radial bone, intra-articular bone remained stable until age 60 years (between 297 and 312 mg HA/cm(3) ) but decreased significantly (p < 0.001) in women thereafter (237.5 ± 44.3) with loss of both cortical and trabecular bone. Similarly, RA patients showed significant (p < 0.001) loss of intra-articular total (263.0 ± 44.8), trabecular (171.2 ± 35.6), and cortical bone (610.2 ± 62.0) compared with sex- and age-adjusted controls. Standard sex- and age-dependent values for physiological intra-articular bone were defined. Postmenopausal state and RA led to significant decrease of intra-articular bone. © 2016 American Society for Bone and Mineral Research.
EVALuna:33251

Bone Mass, Bone Microstructure and Biomechanics in Patients with Hand Osteoarthritis - Simon, David; Tascilar, Koray; Unbehend, Sara; Bayat, Sara; Berlin, Andreas; Liphardt, Anna-Maria; Meinderink, Timo; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd (Journal of Bone and Mineral Research, 2020)
The impact of primary hand osteoarthritis (HOA) on bone mass, microstructure, and biomechanics in the affected skeletal regions is largely unknown. HOA patients and healthy controls (HCs) underwent high-resolution peripheral quantitative computed tomography (HR-pQCT). We measured total, trabecular, and cortical volumetric bone mineral densities (vBMDs), microstructural attributes, and performed micro–finite element analysis for bone strength. Failure load and scaled multivariate outcome matrices from distal radius and second metacarpal (MCP2) head measurements were analyzed using multiple linear regression adjusting for age, sex, and functional status and reported as adjusted Z-score differences for total and direct effects. A total of 105 subjects were included (76 HC: 46 women, 30 men; 29 HOA: 23 women, six men). After adjustment, HOA was associated with significant changes in the multivariate outcome matrix from the MCP2 head (p <.001) (explained by an increase in cortical vBMD (Δz = 1.07, p =.02) and reduction in the trabecular vBMD (Δz = −0.07, p =.09). Distal radius analysis did not show an overall effect of HOA; however, there was a gender-study group interaction (p =.044) explained by reduced trabecular vBMD in males (Δz = −1.23, p =.02). HOA was associated with lower failure load (−514 N; 95%CI, −1018 to −9; p = 0.05) apparent in males after adjustment for functional status. HOA is associated with reduced trabecular and increased cortical vBMD in the MCP2 head and a reduction in radial trabecular vBMD and bone strength in males. Further investigations of gender-specific changes of bone architecture in HOA are warranted. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.
CRIS-Team Scopus Importer:2020-06-09
Keywords: ANALYSIS/QUANTITATION OF BONE; BIOMECHANICS; BONE QCT/MICROCT; DISEASES AND DISORDERS OF/RELATED TO BONE; ORTHOPAEDICS; OSTEOARTHRITIS

Cortical bone loss is an early feature of nonradiographic axial spondyloarthritis - Neumann, Anna; Haschka, Judith; Kleyer, Arnd; Schuster, Louis; Englbrecht, Matthias; Berlin, Andreas; Figueiredo, Camille P.; Simon, David; Muschitz, Christian; Kocijan, Roland; Resch, Heinrich; Rech, Jürgen; et al. (Arthritis Research & Therapy, 2018)
BACKGROUND: In the present study, we investigated bone geometry, microstructure, and volumetric bone mineral density (vBMD) in a cohort of patients with nonradiographic axial spondyloarthritis (nr-axSpA) in order to define the early bone changes occurring in axial spondyloarthritis (axSpA) and to define potential factors for deterioration of bone microstructure. METHODS: Patients with axSpA (n = 107) and healthy control subjects (n = 50) of similar age and sex were assessed for geometric, volumetric, and microstructural parameters of bone using high-resolution peripheral quantitative computed tomography (HR-pQCT) at the radius. Additionally, demographic and disease-specific characteristics of patients with axSpA were recorded. RESULTS: Patients with nr-axSpA and control subjects were comparable in age, sex, and body mass index. Geometric and microstructural analysis by HR-pQCT revealed a significantly reduced cortical area (p = 0.022) and cortical thickness (p = 0.006) in patients with nr-axSpA compared with control subjects. Total and cortical vBMD were significantly reduced in patients with nr-axSpA (p = 0.042 and p = 0.007, respectively), whereas there was no difference in trabecular vBMD. Patients with a short disease duration (< 2 years; n = 46) also showed significant reduction of cortical thickness and cortical area compared with control subjects. Patients with disease duration > 2 years (n = 55) additionally developed a decrease of cortical and total vBMD. Multiple regression models identified male sex to be associated with lower cortical vBMD and female sex to be associated with lower trabecular vBMD. CONCLUSIONS: Bone microstructure in patients with nr-axSpA is characterized primarily by deterioration of cortical bone. Cortical bone loss starts early and is evident within the first 2 years of the disease.
EVALuna2:34667

IMPACT OF PRIMARY HAND OSTEOARTHRITIS ON MICROSTRUCTURE AND BIOMECHANICS IN FINGER JOINTS - Simon, David; Tascilar, Koray; Unbehend, Sara; Bayat, Sara; Meinderink, Timo; Berlin, Andreas; Rech, Jürgen; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-16

INCREASE OF CORTICAL MICRO-CHANNELS (COMICS) AS A NEW FEATURE OF STRUCTURAL DAMAGE IN PAIENTS WITH RHEUMATOID ARTHRITIS - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, F.; Berlin, Andreas; Haschka, J.; Renner, Nina; Buder, Thomas; Rech, Jürgen; Engelke, Klaus; Hueber, Axel; Schett, Georg; et al. (2017)
EVALuna2:34454

Rheumatoid arthritis is characterized by early changes of the cortical micro-channel (CoMiC) system in the bare area of the joints - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Haschka, Judith; Renner, Nina; Buder, Thomas; Engelke, Klaus; Hueber, Axel; Rech, Jürgen; et al. (Arthritis and Rheumatology, 2017)
To characterize the specific structural properties of the erosion-prone bare area of the human joint and to search for early microstructural changes in this region during rheumatoid arthritis Methods: An initial cadaveric study was used for exact localization of the bare area of the metacarpal heads, detection of cortical micro-channels (CoMiCs) in this region by high-resolution peripheral computed tomography (HR-pQCT) and, after anatomical dissection, their validation by micro-computed tomography (?CT). In the second part, number and distribution of CoMiCs were analyzed in 105 healthy individuals and 107 RA patients with similar sex and age distribution.HR-pQCT investigation combined with adaptive thresholding allowed detection of CoMiCs in the bare area of cadaveric joints. Their existence in the bare area was additionally validated by ?CT. In healthy individuals, the number of CoMiCs increased with age. RA patients showed significantly (p<0.001) more CoMiCs (112.9±54.7/joint) than healthy individuals (75.2±41.9/joint) with 20-49 years old RA patients exhibiting similar CoMiC numbers as observed in over 65 year old healthy individuals. Importantly, CoMiCs were found in RA patients already very early in their disease course with enrichment in the erosion-prone radial side of the joint.CoMiCs represent a new form of structural change in the joints of patients with RA. While CoMiCs increase with age, RA patients develop such changes much earlier in life and already at the onset of the disease. CoMiCs therefore represent an interesting new opportunity to assess structural changes in RA. This article is protected by copyright. All rights reserved.
EVALuna2:13409

Simultaneous quantification of bone erosions and enthesiophytes in the joints of patients with psoriasis or psoriatic arthritis - effects of age and disease duration - Simon, David; Kleyer, Arnd; Faustini, Francesca; Englbrecht, Matthias; Haschka, Judith; Berlin, Andreas; Kraus, Sebastian; Hueber, Axel; Kocijan, Roland; Sticherling, Michael; Rech, Jürgen; Schett, Georg (Arthritis Research & Therapy, 2018)
BACKGROUND: Comprehensive simultaneous quantification of bone erosion and enthesiophytes in the joints of patients with psoriatic arthritis (PsA) has not been performed. Herein, we aimed to compare the extent of bone erosion and enthesiophytes in patients with PsA, psoriasis (PSO) and healthy controls, assess the influence of age and disease duration on the development of erosions and enthesiophytes and define their impact on physical function. METHODS: Patients with PsA or with PSO and controls were analysed by high-resolution peripheral quantitative computed tomography (HR-pQCT). The extent of bone erosions and enthesiophytes was assessed and plotted according to different categories of age, duration of PSO and duration of PsA, respectively. In addition, demographic and disease-specific data, including physical function (health assessment questionnaire) were collected. RESULTS: A total of 203 patients were analysed; 101 had PsA, 55 had PSO and 47 were healthy individuals. Patients with PsA had significantly more and larger erosions (p = 0.002/p = 0.003) and enthesiophytes (p < 0.001) compared to patients with PSO and healthy controls. Patients with PSO and healthy controls did not differ in erosions, while enthesiophytes were more frequent in patients with PSO than in healthy controls. Bone erosions, but not enthesiophytes, showed strong age-dependency in all three groups. In contrast, enthesiophytes were mostly influenced by the duration of PSO and PsA and, in contrast to bone erosions, were associated with poorer physical function. CONCLUSIONS: Bone erosions are age-dependent, enhanced in PsA and increase with disease duration. Enthesiophytes are less age-dependent, are enhanced in both PSO and PsA and strongly influenced by disease duration. Enthesiophytes impact physical function in PsA suggesting the need for early therapeutic interventions to prevent damage.
EVALuna2:34666

The ageing joint-standard age- and sex-related values of bone erosions and osteophytes in the hand joints of healthy individuals - Berlin, Andreas; Simon, David; Tascilar, K.; Figueiredo, C.; Bayat, Sara; Finzel, Stephanie; Klaus, E.; Rech, Jürgen; Hueber, Axel; Kleyer, Arnd; Schett, Georg (Osteoarthritis and Cartilage, 2019)
Objective: To analyze the age-related changes of the physiological hand joint architecture. Method: To address this concept, healthy individuals (each 10 women and 10 men in six different age decades spanning from 21 to 80 years) were recruited through a field campaign, investigated for the absence of rheumatic diseases and other comorbidities and received high-resolution quantitative computed tomography (HR-pQCT) examination of the hand joints. Number and extent of erosions and osteophytes were quantified across the ages and different sexes. Results: Bone erosions [median (Q1–Q3), 1 (0–2)] and osteophytes [2 (1–4)] were found in healthy women and men with no significant sex differences. Structural changes however accumulated with age: the overall incidence rate ratio (IRR) for the number of erosions and osteophytes per age were 1.04 (95% CI: erosions 1.03–1.06; osteophytes: 1.03–1.05). This means a 4% increase in the number of erosions and osteophytes per year. Using third decade as reference, healthy individuals in the age decades from 50 years had higher IRR for erosion numbers (sixth, seventh, eigth decade: 4.87 (2.20–11.75), 6.81 (3.08–16.46) and 6.92 (3.11–16.79)) compared to younger subjects (fourth, fifth decade: 1.80 (0.69–4.87), 1.53 (0.59–4.10)). The IRRs of osteophytes also indicate a gradual increase after the fifth decade, with IRRs of 2.32 (1.32–4.17), 4.17 (2.38–7.49) and 6.86 (3.97–12.20) for the sixth, seventh and eigth decades, respectively. Conclusions: Structural changes in the hand joints of healthy individuals are age dependent. While being rare under 50 years of age, erosions and osteophytes accumulate above the age of 50, suggesting that the threshold between “normal” and “pathological” is shifted with the increase of age.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Bone erosions; Computed tomography; Hand joints; Healthy individuals; Osteophytes

THE PHYSIOLOGICAL FINGER JOINT ARCHITECTURE - AGE-RELATED INCREASE OF EROSIONS AND OSTEOPHYTES IN THE JOINTS OF HEALTHY INDIVIDUALS - Simon, David; Berlin, Andreas; Tascilar, Koray; Bayat, Sara; Engelke, Klaus; Rech, Jürgen; Figuereido, Camille; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-07-12